2020
DOI: 10.3390/medicina56080399
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnoea in Patients Treated for Head and Neck Cancer: A Systematic Review of the Literature

Abstract: Background and objectives: Obstructive sleep apnoea (OSA) is clinically defined by signs of daytime sleepiness and objective measures of disordered breathing during sleep. The literature is still controversial on the incidence and aetiology of OSA secondary to head and neck cancer treatment. The aim of this systematic review is to evaluate and discuss the prevalence of OSA in patients treated with surgery and/or chemo/radiotherapy for head and neck cancer. Materials and methods: Following the Preferred Reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…Since our patients, along with the intraoral resection, underwent modified radical neck dissection and reconstruction with the bulky the pectoralis major myocutaneus flap, it can be implicated that due to the changed anatomical and neuromuscular relations, they could possibly have a higher prevalence of obstructive sleep apnea. Moreover, recent systematic review results suggested that head and neck cancer patients have a higher incidence of obstructive sleep apnea when compared to the general population [ 47 ]. However, these results should be taken with caution since the exact etiology and subsequent correct management in these patients still needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Since our patients, along with the intraoral resection, underwent modified radical neck dissection and reconstruction with the bulky the pectoralis major myocutaneus flap, it can be implicated that due to the changed anatomical and neuromuscular relations, they could possibly have a higher prevalence of obstructive sleep apnea. Moreover, recent systematic review results suggested that head and neck cancer patients have a higher incidence of obstructive sleep apnea when compared to the general population [ 47 ]. However, these results should be taken with caution since the exact etiology and subsequent correct management in these patients still needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we discovered that the incidence of OSA among patients with OOCs before surgery was 91.3%, which was considerably higher than that in individuals without such cancer. 6 , 7 According to an epidemiological survey on OSA, 6 the prevalence of OSA for men and females in European and American countries was 17%–26% and 9%–50%, respectively; in Asian countries, it was 8.8%–37.4% and 3.7%–16%, respectively; and globally, it was 22% and 17%, respectively. This may be because the tumor in the respiratory tract narrows the respiratory tract, thereby increasing airflow resistance.…”
Section: Discussionmentioning
confidence: 99%
“…OSA, as well as HNSCC, causes poor quality of life. In a systematic review of 10 prospective studies on the subject, OSA incidence ranged from 12% to 95.8%, with a weighted average of 59.78% on patients treated for head and neck cancer [22].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer ranks among the top ten most common types of cancer worldwide with a severe impact on quality of life and elevated mortality in affected individuals [20,21]. Although there appears to be an elevated OSA incidence in patients with head and neck cancer, this comorbidity and particularly its possible linkage has been poorly studied in small prospective studies [22].…”
Section: Introductionmentioning
confidence: 99%